Verification benchmarks for single-phase flow in three-dimensional fractured porous media. (January 2021) - Berre, Inga; Boon, Wietse M.; Flemisch, Bernd; Fumagalli, Alessio; Gläser, Dennis; Keilegavlen, Eirik; Scotti, Anna; Stefansson, Ivar; Tatomir, Alexandru; Brenner, Konstantin; Burbulla, Samuel; Devloo, Philippe; et al.
Highlights: Presents four benchmark cases for single-phase flow in three-dimensional fractured porous media. Investigates the capabilities of DFM methods in handling complexities common to fracture networks. Compares results of 17 different numerical methods, submitted by 11 participating groups. Is supplemented by a public Git repository containing result data and reproducing Jupyter notebooks. Abstract: Flow in fractured porous media occurs in the earth's subsurface, in biological tissues, and in man-made materials. Fractures have a dominating influence on flow processes, and the last decade has seen an extensive development of models and numerical methods that explicitly account for their presence. To support these developments, four benchmark cases for single-phase flow in three-dimensional fractured porous media are presented. The cases are specifically designed to test the methods' capabilities in handling various complexities common to the geometrical structures of fracture networks. Based on an open call for participation, results obtained with 17 numerical methods were collected. This paper presents the underlying mathematical model, an overview of the features of the participating numerical methods, and their performance in solving the benchmark cases.